2003
DOI: 10.1159/000073847
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Controlled Study of a Computer-Assisted Acenocoumarol Dosage Program

Abstract: The increase in oral anticoagulant (OA) treatment has led to development of new strategies for its control. We tested the efficacy of the GAO software (Dade Behring) in providing adequate acenocoumarol dosages for patients whose international normalised ratios (INRs) were no more than 0.5 points out of range. From December 1998 to August 1999, all outpatients in this setting were randomly assigned to receive computer-generated or traditionally fixed OA doses. Patients in their first 4 weeks of treatment were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
1
4
0
4
Order By: Relevance
“…This percentage of INR controls in range is similar to the obtained in an observational study including Italian and Spanish patients (the most active countries recruiting patients in RIETE), in which the TTR were 68.9% and 64.4%, respectively (26). Similar estimates were observed in two other studies (27,28). Thus, at least in our setting, the TTR in daily practice would not significantly differ from those observed in the setting of the clinical trials included in the a aforementioned systematic review (11).…”
Section: What Does This Paper Add?supporting
confidence: 89%
“…This percentage of INR controls in range is similar to the obtained in an observational study including Italian and Spanish patients (the most active countries recruiting patients in RIETE), in which the TTR were 68.9% and 64.4%, respectively (26). Similar estimates were observed in two other studies (27,28). Thus, at least in our setting, the TTR in daily practice would not significantly differ from those observed in the setting of the clinical trials included in the a aforementioned systematic review (11).…”
Section: What Does This Paper Add?supporting
confidence: 89%
“…46,[78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97] These dosing adjuncts have been studied at the initiation of therapy (no prior VKA doses) and during the maintenance phase of therapy and were compared with dose deci sions made without the use of decision support (manual dosing). Both nomogram/computer-assisted and manual dosing were performed by experienced anticoagulation providers in some studies 78,86,87,90,91 and by providers without specialized training (eg, trainee physicians, house staff, regular physician, nurses) in others. 46,[79][80][81][82][83][84][85]88,89,[92][93][94][95] Decision support-guided dosing (paper nomograms or computer programs) performed no better than manual dosing during initiation of VKA therapy in pooled analyses of available RCTs ( Table 7 , Table S7).…”
Section: Dosing Decision Supportmentioning
confidence: 99%
“…1,9 Dosing Nomograms Several reports have summarized experience with computerassisted dosage programs used to assist VKA dosing. [17][18][19][20][21][22][23] Although the use of such software programs is likely increasing, less than 5% of surveyed physicians indicated that they used a computer-assisted dosing program in their usual VKA dosing practices. 24 Use of computer-assisted dosing support increased to 9% when the responsibility for warfarin dosing was delegated to a nonphysician staff member.…”
Section: Inr Recall Intervalmentioning
confidence: 99%